THE EFFECT OF LEADERSHIP COMMUNICATION AND EMPLOYEE WELL-BEING WITH EMPLOYEE TRUST AS A MEDIATOR ON SUPPORT OF ORGANIZATIONAL CHANGE - Nurhayati Nurhayati; Dewie Tri Wijayati Wardoyo; Jun Surjanti (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The research goal is to investigate how leadership communication, employee well-being, and employee trust impact the support for organizational change. This quantitative study involved 112 participants and looked at how variables such as leadership communication, employee well-being, employee trust, and organizational change support are connected. Data was gathered through a questionnaire using a Likert scale from 1 to 5, representing degrees of disagreement or agreement. The collected data was then analyzed using the SMART_PLS software. There is a supposed influence between leadership communication and the support of organizational change. (2) Communication from leaders has an impact on the level of trust employees have within the company. (3) There is the influence of employee well-being and support of organizational change, (4) there is a presumption between employee welfare and employer trust in an organization. (5) There are influences among employees trust in support of organizational change, (6) Employee Trust is the mediator of leadership communication and support for organizational changes, and (7) Employees trust is the intermediary of employment trusts and supports organizational change